2021
DOI: 10.17509/ijal.v10i3.31749
|View full text |Cite
|
Sign up to set email alerts
|

The representation of cultural values in Korean as a foreign language (KFL) textbook

Abstract: The representation of cultural values in textbooks is crucial to be examined because learning a foreign language is bound with the culture. Although previous research has quite extensively investigated this issue, much is yet to be explored in the context of Korean as a foreign language learning. This study aims to address the gap by investigating how cultural values are represented in the Korean as a foreign language (KFL) textbook, published by The Korea Foundation for Indonesians. A critical discourse analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The quality of textbooks also contributes to success in learning a second language. Textbooks are a medium for building knowledge and understanding of second language learners and as a guide in implementing learning (Sun and Dang, 2020;Samsudin et al, 2021;Pratiwi et al, 2022). Based on this, second language teachers can adapt textbook material by adjusting it to the circumstances and context of learning.…”
Section: Textbooks In Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of textbooks also contributes to success in learning a second language. Textbooks are a medium for building knowledge and understanding of second language learners and as a guide in implementing learning (Sun and Dang, 2020;Samsudin et al, 2021;Pratiwi et al, 2022). Based on this, second language teachers can adapt textbook material by adjusting it to the circumstances and context of learning.…”
Section: Textbooks In Language Learningmentioning
confidence: 99%
“…Concerning learning a second language, this study has found many studies that examine moral values in textbooks as learning resources. These studies include moral values in English learning textbooks (Tajeddin and Teimournezhad, 2015;Mcconachy, 2018;Sulistiyo et al, 2020;Puspitasari et al, 2021), moral values in Korean language learning textbooks (Samsudin et al, 2021), and moral values in Japanese language learning textbooks (Nishino, 2019). Meanwhile, this study has not found a reference source that examines moral values in Indonesian language textbooks for Foreign Speakers (often known as BIPA).…”
Section: Introductionmentioning
confidence: 96%
“…Other studies examining textbook material in relation to its cultural setting have been conducted by several scholars (Butar-butar & Pasaribu, 2021;Samsudin, Ansas, & Triarisanti, 2021;Ariawan, 2020;Kim & Ma, 2018). Butar-butar & Pasaribu (2021) conducted a comparison of English textbooks published by domestic and international publishers in terms of the sort of culture and dimensions included in the two textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ariawan (2020) investigated the cultural dimension in EFL textbook. Moreover, Kim & Ma (2018) and Samsudin et al (2021) studied the cultural content of textbooks in South Korea. He examined portrayals of American and South Korean culture in Korean high school textbooks.…”
Section: Introductionmentioning
confidence: 99%